Respiratory syncytial virus infection. Case report of patients in the critical pediatric area of ​​a hospital in northern Perú - Becerra-Gutiérrez, Lizzie K. (2022)
Background: The respiratory syncytial virus (RSV) responsible for pneumonia and cause of hospitalization in critical pediatric areas, can cause deaths in infants. Report of case: Five infrequent cases were analyzed at a seasonal level in a hospital in northern Peru during the period from April to June 2019, where patients with pneumonia caused by RSV were observed, confirmed by direct immunofluorescence, chest radiography and with the presence of associated clinical findings hepatomegaly and atelectasis. Of the 05 cases: 4 correspond to boys and a girl, aged 2-7 months, all were hospitalized, presented wheezing, crackles and polytirage as prevalent signs at admission, all developed severe pneumonia and complications, were recorded two deaths in children under 6 months of age, with complications of sepsis, PARDS, and mechanical ventilation. Conclusion: the cases reflect characteristic clinical pictures of the disease, pneumonia and atelectasis in infants, complications such as SOB, PARDS and hepatomegaly.